The Turkish Retranslations of Marx's Das Kapital as a Site of Intellectual and Ideological Struggle - (:unkn) unknown (SPRINGER-VERLAG SINGAPORE PTE LTD, 2019)
This chapter discusses the retranslations of Karl Marx's Das Kapital into Turkish starting with the earliest attempt to partially translate the work in 1912 and explores how the translation of this particular book became a site of intellectual and ideological struggle among translators and publishers. The analysis will be carried out on the basis of paratextual material, i.e. prefaces to the various translations as well as critical essays by translators and publishers. The struggle over translations of Das Kapital in Turkey releases the tension between agents involved in the translation and publication of the work as manifested both by a discussion on the issues of terminology and concepts (aimed at the formation of a Turkish leftist discourse) and on the 'correct reading' of the text itself. Likewise, the account of the ban on the work imposed in 1938 during the single-party regime, lifted in 1965 following an appeal by the Turkish Workers Party (TIP - Turkiye Isci Partisi) to the Constitutional Court, serves to display how this major work has gained its 'freedom' from censorship relatively earlier than Manifest der Kommunistischen Partei (The Communist Manifesto), another seminal Marxist work.